Sosiolek Variasi Bahasa Pedagang Dipasar Talang Banjar Kota Jambi - Agung Yusup; Neldi Harianto; Sri Wahyu Ningsih (Fakultas Keguruan dan Ilmu Pendidikan,Universitas Jambi, 2023)
Indonesian is rich in diversity so that in sociolinguitic studies there is a discussion of sociolects. sosiolek is a variation of language that comes from groups of people who have differences in the level of social status, position, class, and social class by the speakers themselves. With that researchers chose a group of traders in Pasar Talang Banjar as the object of research. The market is one of the markets located in the middle of the city of Jambi. In this study the researchers used qualitative methods and make observations and record video directly at the location of the market so as to obtain concrete evidence. From the results of the study found that one of the factors that cause not many language variations arise in Talang Banjar market is due to geographical factors and the local population around the market that has varied there are natives of jambi, Java, batak, chinnes descendants so that in buying and selling transactions traders more often use the jambi language that is not so thick and Indonesian is not standard as a unifier. Language variations that occur in the speech of traders generally occur due to factors of language users themselves and their use factors. In terms of language users, language variation occurs due to geographical factors that cause regional variations (dialects). In addition, in terms of users, language variation also occurs due to the influence of speech opponents. In terms of the use of language, language variations in terms of the topic of the problem, generally traders always say quantity (amount)